Creatively hateful labelling of the “Other”: Neologisms in internet comments - Jūratė Ruzaitė (Studii de Lingvistica)
So far, neologisms have been analysed in relation to hateful and aggressive content to a very limited extent and often in a fragmented manner. This paper focuses on the language of “othering” as a central component of hate speech, examining it in Lithuanian internet comments. Special emphasis is placed on neologisms, which serve as creative linguistic forms used to express “othering”. The dataset consists of 10,662 comments, totalling 284,226 tokens. In order to assess the level of creativity associated with different degrees of hostility, the data encompasses neutral comments, offensive comments, and those containing potentially illegal hate speech. The research findings are presented by examining the distribution of neologisms across the three types of comments and analysing the types of neologisms employed to create novel forms referring to the Other.